Mouse oocytes nucleoli rescue embryonic development of porcine enucleolated oocytes - Morovic, Martin; Strejcek, Frantisek; Nakagawa, Shoma; Deshmukh, Rahul S; Murin, Matej; Benc, Michal; Fulka, Helena; Kyogoku, Hirohisa; Pendovski, Lazo; Fulka, Josef; Laurincik, Jozef (Zygote (Cambridge, England), 2017)
It is well known that nucleoli of fully grown mammalian oocytes are indispensable for embryonic development. Therefore, the embryos originated from previously enucleolated (ENL) oocytes undergo only one or two cleavages and then their development ceases. In our study the interspecies (mouse/pig) nucleolus transferred embryos (NuTE) were produced and their embryonic development was analyzed by autoradiography, transmission electron microscopy (TEM) and immunofluorescence (C23 and upstream binding factor (UBF)). Our results show that the re-injection of isolated oocyte nucleoli, either from the pig (P + P) or mouse (P + M), into previously enucleolated and subsequently matured porcine oocytes rescues their development after parthenogenetic activation and some of these develop up to the blastocyst stage (P + P, 11.8%; P + M, 13.5%). In nucleolus re-injected 8-cell and blastocyst stage embryos the number of nucleoli labeled with C23 in P + P and P + M groups was lower than in control (non-manipulated) group. UBF was localized in small foci within the nucleoli of blastocysts in control and P + P embryos, however, in P + M embryos the labeling was evenly distributed in the nucleoplasm. The TEM and autoradiographic evaluations showed the formation of functional nucleoli and de novo rRNA synthesis at the 8-cell stage in both, control and P + P group. In the P + M group the formation of comparable nucleoli was delayed. In conclusion, our results indicate that the mouse nucleolus can rescue embryonic development of enucleolated porcine oocytes, but the localization of selected nucleolar proteins, the timing of transcription activation and the formation of the functional nucleoli in NuTE compared with control group show evident aberrations.
Keywords: prasata; Swine; blastocysta; embryo savčí; Embryo; oocyty; Cloning, Organism; Cell Nucleolus; Embryonic Development; Interspecies nucleolar transfer; Pregnancy; těhotenství; klonování organismů; Embryo, Mammalian; Mouse; oogeneze; Animals; ženské pohlaví; přenos embrya; Pig; zvířata; embryonální vývoj; myši; Embryo Transfer; Nucleolus; Mice; Female; Blastocyst; buněčné jadérko; Oogenesis; Oocytes